Analisis Gaya Kepemimpinan Perempuan Di Dinas Sosial Kota Bengkulu (Studi Pada Kepala Bidang Penanganan Fakir Miskin Dengan Kepala Bidang Perlindungan Dan Jaminan Sosial) - Astuti, Nanda Gita Puji; Sakti, Budiman; Purnawan, Heru (SENGKUNI Journal (Social Science and Humanities Studies), 2024)
Based on the analysis and findings obtained in the field during research related to the Analysis of Women's Leadership Style at the Bengkulu City Social Service (Study on the Head of the Poor Handling Division with the Head of the Social Protection and Security Division) it can be said that women's leadership style is not inferior to male leadership.Â  This is evident from the many women who are leaders in agencies or institutions. That female leaders generally have strong charisma, like male leadership.Â  Women leaders tend to be persuasive, confident, and have a strong ability to complete tasks and are energetic, The female leadership style implemented by the Head of the Poverty Handling Division, has several key characteristics. She believes that women have the innate potential to be leaders and that confidence and good looks are important factors in women's leadership.